2013
DOI: 10.1371/journal.pone.0079883
|View full text |Cite
|
Sign up to set email alerts
|

Mice Overexpressing β-1,4-Galactosyltransferase I Are Resistant to TNF-Induced Inflammation and DSS-Induced Colitis

Abstract: Glycosylation is an essential post-translational modification, which determines the function of proteins and important processes such as inflammation. β-1,4-galactosyltransferase I (βGalT1) is a key enzyme involved in the addition of galactose moieties to glycoproteins. Intestinal mucins are glycoproteins that protect the gut barrier against invading pathogens and determine the composition of the intestinal microbiota. Proper glycosylation of mucus is important in this regard. By using ubiquitously expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
2
9
0
2
Order By: Relevance
“…Furthermore, bacterial adhesion to mucin glycans may be a mechanism by which the host selects bacterial species that present the complementary set of adhesins ( 86 ). The link between glycosylation of the intestinal mucus layer and microbiota composition has been highlighted in studies using mouse models deficient in specific mucin glycosyltransferase genes ( 87 93 ). Furthermore, recent work showed that host-derived fucose signaling, activated through the microbiota, can modulate pathogenic intestinal colonization ( 94 , 95 ) indicating that mucin glycosylation has a selective capacity on microbial ecology.…”
Section: Factors Influencing Infant Microbiota Developmentmentioning
confidence: 99%
“…Furthermore, bacterial adhesion to mucin glycans may be a mechanism by which the host selects bacterial species that present the complementary set of adhesins ( 86 ). The link between glycosylation of the intestinal mucus layer and microbiota composition has been highlighted in studies using mouse models deficient in specific mucin glycosyltransferase genes ( 87 93 ). Furthermore, recent work showed that host-derived fucose signaling, activated through the microbiota, can modulate pathogenic intestinal colonization ( 94 , 95 ) indicating that mucin glycosylation has a selective capacity on microbial ecology.…”
Section: Factors Influencing Infant Microbiota Developmentmentioning
confidence: 99%
“…The reason is that the process of glycosylation modification is dynamic (Suryavathi et al, 2015 ; Moratz et al, 2017 ), and the connection of glycans is varied. At present, the researches about β-1, 4 galactosyltransferase mainly concentrate in β4GalT1 (Vanhooren et al, 2013 ; Sun et al, 2014 ), especially apoptosis-related regulatory mechanisms (Yuan et al, 2012 ). The studies of β4GalT2-7 remain to be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic β-1,4-galactosyltransferase I (βGalT1) enzyme plays an essential role in N-glycosylation, catalyzing the addition of galactose to N-acetylgalactosamine of type 2 N-glycans. In addition, mice overexpressing βGalT1 have a decreased predisposition to dextran sodium sulfate (DSS)-induced colitis, owing to an elevated Firmicutes-to-Bacteroidetes ratio [41].…”
Section: Physiological Significance Of Mucin Glycansmentioning
confidence: 99%